1976
DOI: 10.1128/jb.126.1.377-383.1976
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of the regularly arranged surface layers of Clostridium thermosaccharolyticum and Clostridium thermohydrosulfuricum

Abstract: Clostridum thermosaccharolyticum and Clostridiurm thermohydrosulfuricum possess as outermost cell wall layer a tetragonal or hexagonal ordered array of macromolecules. The subunits of the surface layer can be detaqhed from isolated. cell walls with urea (8 M) or guanidine-HCl (4 to 5 M). Triton X-100, dithiothreitol, ethylenediaminetetraacetate, and KCl (3 M) had no visible effect on the regular arrays. Sodium dodecyl sulfate-polyacrylamide electrophroesis showed that, in both organisms, the surface layer is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 23 publications
3
42
0
Order By: Relevance
“…Freeze-etched preparations of intact cells of C. thermosaccharolyticum showed the presence of a square surface-layer lattice ( Fig. 1 a), as already demonstrated by Sleytr and Thorne [5]. Thin sections confirmed the location of the surface layer as the outermost cell envelope component ( Fig.…”
Section: Surface Layer Structuresupporting
confidence: 77%
See 3 more Smart Citations
“…Freeze-etched preparations of intact cells of C. thermosaccharolyticum showed the presence of a square surface-layer lattice ( Fig. 1 a), as already demonstrated by Sleytr and Thorne [5]. Thin sections confirmed the location of the surface layer as the outermost cell envelope component ( Fig.…”
Section: Surface Layer Structuresupporting
confidence: 77%
“…Growth of bacteria and isolation of the glycopeptide C. thermosaccharolyticum D120-70 was grown as described and the surface-layer glycoprotein was isolated from clean cell walls by extraction with 5 M guanidine hydrochloride [5]. Upon thorough dialysis of this extract three times against 2 1 distilled water, self-assembly products consisting of pure surface-layer glycoprotein subunits were formed [5]. The glycopeptides were obtained after pronase digestion (1 5% pronase) as described previously [8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The localization of the high-molecular-mass component of the cell wall of C. tyrobutyricum is not yet known. However, many bacteria including Clostridium species are known to possess regular arrays composed of hexagonally or tetragonally arranged protein subunits of high molecular mass on the outer surface of their cell walls [15], Authors in [16] observed an ordered layer of glycoprotein of 140 kDa in C. tbermosaccbaro~yticum and thermohydrosuffuricum and those in f 171 also observed an ordered layer of protein of 195 kDa on C.botulinum type A. In the case of C. tyrobutyricum, such regular arrays have not yet been demonstrated but the high-molecular-mass component found in its cell wall may perhaps belong to a structure of this type.…”
Section: Discussionmentioning
confidence: 99%